Complex gas kinematics in compact, rapidly assembling star-forming galaxies - Amorín, R. (2012)
Deep, high-resolution spectroscopic observations have been obtained for six compact, strongly star-forming galaxies at redshift z ∼ 0.1–0.3, most of them also known as green peas. Remarkably, these galaxies show complex emission-line profiles in the spectral region including Hα, [N ii] λλ6548, 6584, and [S ii] λλ6717, 6731, consisting of the superposition of different kinematical components on a spatial extent of few kiloparsecs: a very broad line emission underlying more than one narrower component. For at least two of the observed galaxies some of these multiple components are resolved spatially in their two-dimensional spectra, whereas for another one a faint detached Hα blob lacking stellar continuum is detected at the same recessional velocity ∼7 kpc away from the galaxy. The individual narrower Hα components show high intrinsic velocity dispersion (σ ∼ 30–80 km s−1), suggesting together with unsharped masking Hubble Space Telescope images that star formation proceeds in an ensemble of several compact and turbulent clumps, with relative velocities of up to ∼500 km s−1. The broad underlying Hα components indicate in all cases large expansion velocities (full width zero intensity ⩾1000 km s−1) and very high luminosities (up to ∼1042 erg s−1), probably showing the imprint of energetic outflows from supernovae. These intriguing results underline the importance of green peas for studying the assembly of low-mass galaxies near and far.